Balancing Language Learning with Translanguaging: Insights from Yunnan Agricultural University - Xin, Ke; Yap, Teng Teng (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
This study investigates the strategic application of translanguaging in English classes at Yunnan Agricultural University, a context marked by significant linguistic diversity and socio-economic challenges that have been underexplored. Employing a mixed-methods approach, the research integrates quantitative surveys and qualitative interviews to provide comprehensive analysis. Grounded in Vygotsky’s sociocultural theory, which emphasizes the importance of social interaction and cultural context in cognitive development, the study reveals that translanguaging significantly enhances comprehension and reduces stress for students across varying levels of English proficiency. However, it also identifies potential risks associated with excessive reliance on native languages, which may hinder the development of critical cognitive abilities necessary for English language acquisition. The findings underscore the importance of a balanced approach to translanguaging, where strategies are carefully adapted to the unique linguistic, cultural, and institutional contexts of learners. This research highlights the need for further exploration into how translanguaging strategies can be optimized to support both critical thinking and language comprehension in diverse educational settings.